Analisis Karakteristik Peserta Didik - Ahmad Taufik (El-Ghiroh : Jurnal Studi Keislaman, 2019)
a teacher in conducting the learning planning process needs to understand the characteristics and initial abilities of students. Analysis of learners' initial abilities is an activity of identifying learners in terms of needs and characteristics to determine behavioral or goal and material specifications and qualifications.Interaction between teacher and students, students and others are no longer unilateral but are more emotional and sympathetic or interactive relationships through the teaching and learning process. Students are no longer an object of education but have been reduced to polarization of thinking by stating that students as students, a fun and exciting interaction process makes learning effective.